Development of a multi-neoepitope vaccine targeting non-small cell lung cancer through reverse vaccinology and bioinformatics approaches - Asadollahi, Elahe; Zomorodipour, Alireza; Soheili, Zahra-Soheila; Jahangiri, Babak; Sadeghizadeh, Majid (Frontiers in Immunology, 2025)
IntroductionLung cancer, predominantly non-small cell lung cancer (NSCLC), is the leading cause of cancer-related mortality worldwide. Among immunotherapeutic strategies, the personalized multi-neoepitope vaccine (MNEV) offers a promising approach for managing advanced-stage NSCLC.MethodsWe used reverse vaccinology, immunoinformatics, and bioinformatics to design an MNEV targeting lung cancer in murine (LL/2) cells. Whole exome sequencing (WES) and RNA sequencing data from human and mouse NSCLC cell lines were analyzed to select neoantigens, which were evaluated for their ability to stimulate B cells, helper T lymphocytes (HTLs), and cytotoxic T lymphocytes (CTLs). Molecular docking studies estimated the binding affinity of mouse neoepitopes with MHC class I, MHC class II, and B-cell receptors. Suitable linkers were selected to construct the MNEV, with the 50S L7/L12 ribosomal protein sequence included as an adjuvant to enhance immune responses. The immunoglobulin kappa (Igκ) chain signal peptide was incorporated to improve secretion efficiency. The stability of the final MNEV construct in complex with TLR3, TLR4, and TLR9 was confirmed through binding analysis and refinement of the best-predicted 3D model. To evaluate the immunological efficacy of the MNEV, female C57BL/6 mice were immunized subcutaneously. Immune responses were assessed by measuring total IgG levels in serum using enzyme-linked immunosorbent assay (ELISA) and quantifying IFN-γ and granzyme B levels in the supernatant of cultured splenocytes. The proportions of CD19+ B cells and CD4+ and CD8+ T cells were determined using flow cytometric analysis.ResultsIn silico evaluations indicated that the MNEV is non-toxic, non-allergenic, and stable, exhibiting high-affinity interactions with B lymphocytes, CTLs, and HTLs. Immunization with the MNEV significantly increased serum IgG levels. Flow cytometry analysis revealed higher percentages of CD19+ B cells and CD4+ and CD8+ T cells. Furthermore, splenocytes from immunized mice showed a marked increase in IFN-γ and granzyme B secretion compared to control groups.DiscussionThis study demonstrates that the MNEV induces a robust strong immune response, highlighting its potential as a promising approach for cancer prevention and immunotherapy, particularly for NSCLC. Furthermore, it provides a foundation for developing neoepitope-based vaccines against various malignancies, guiding future research in cancer vaccine development through advanced computational methods in immunology and oncology.